Death attitudes and associated factors among health professional students in China - Han, Huiwu; Ye, Ying; Zhuo, Hongxia; Liu, Shaohui; Zheng, Fan (Frontiers in Public Health, 2023)
Background China is entering an era of aging population with an increased mortality rate among this category of population. Health professional students' attitudes toward death directly affect their quality of palliative care in their future careers. It is thus important to understand their death attitudes and associated factors to guide future educational and training development. Objectives This study aimed to investigate death attitudes and analyze the associated factors among health professional students in China. Methods In this cross-sectional study, 1,044 health professional students were recruited from 14 medical colleges and universities. The Chinese version of the Death Attitude Profile-Revised (DAP-R) was used to evaluate their death attitudes. A multiple linear regression model was used to analyze the influencing factors of attitudes toward death. Results Health professional students tended to accept death more neutrally. Multivariate analysis showed that their negative death attitudes were associated with age (β = −0.31, p < 0.001) and religious belief (β = 2.76, p = 0.015), while positive death attitudes were associated with age (β = −0.42, p < 0.001), hearing of Advance Care Plan (ACP) (β = 2.21, p = 0.001), and attending funeral/memorial services (β = 2.69, p = 0.016). Conclusion Our study stresses the importance of including death and palliative care education in healthcare courses among health professional students in China. Incorporation of ACP education along with experiences of funeral/memorial services may help promote health professional students' positive attitudes toward death and improve the quality of palliative care in their future careers.